Youth mental health services in Italy: An achievable dream?. Issue 3 (8th April 2016) - Masillo, Alice; Brandizzi, Martina; Nelson, Barnaby; Lo Cascio, Nella; Saba, Riccardo; Lindau, Juliana Fortes; Telesforo, Ludovica; Montanaro, Dori; D'Alema, Marco; Girardi, Paolo; McGorry, Patrick; Fiori Nastro, Paolo
Abstract: Aim: "Liberiamo il futuro" (LIF) project was designed to assess psychological problems of adolescents and young adults and to identify individuals at high‐risk for developing a psychosis through a collaboration between a University team, Child and Adolescent Mental Health Services and Adult Mental Health Services. This paper presents the baseline demographic and clinical characteristics of the cohort, particularly the nature and severity of psychopathology. Method: All help‐seeking young people aged 12–35 years residing in the health district involved in LIF were invited to participate in the study and completed a battery of self‐ report and interviewer‐administered measures of psychopathology and functioning at baseline. Results: A total of 338 adolescents and young people (mean age 17.42) participated in the study. The majority of the sample ( n  = 107, 35%) had an anxiety disorder, followed by mood disorders ( n  = 62, 21%). Only 35 (12%) participants had no psychiatric diagnosis. After a screening phase, 166 (52%) individuals were assessed to detect the presence of an Ultra High Risk (UHR) state. Of these, 38.60% ( n  = 64) met UHR criteria. Overall, the majority of the sample resulted moderately functionally impaired at baseline. Conclusions: LIF project showed that psychological problems, associated with impaired psychosocial functioning, are very common among help‐seeking young people. The help‐seeking behaviour of young people is in contrast with the barriers presented by the Italian community mental health system that is modelled around adults' requirements. A need of a strong, stigma‐free, young oriented system of care for young people up to the mid‐20s emerged.